The Influence of Family Strength on the Quality of Pregnancy - Euis Sunarti; Hidayat Syarief; Hardinsyah .; Ratna Megawangi; Asep Saefuddin; Husaini . (Media Gizi dan Keluarga, 2003)
The Objectives of this study were to anaylize the influence of family strength on pregnancy quality. The data were analyzed from the study of "Effect of multinutrient fortified food suplement on pregnancy outcomes", which had been done previously by the Departement of Community Nutrition and Family Resources of IPB. Some additional information on family strength was also collected retrospectively. Of the 615 pregnant mothers in Luwiliang district (19 villages) and Cibungbulang district (15 villages), 233 mothers met the sample criterias were selected Pregnancy quality was measured by pregnancy weight gain. Family strength data (q=0.7) consisted of informations on physical resources, non-physical resources. Family problems, capping mechanism, physical well-being, social well-being, and psychologycal well-being. Applying a multiple linear regression model, body weight at the beginning of pregnancy and family strength has a significant effect on pregnancy weight gain. The items of Family strength are health factor, family goal, free from anger, and social support. The above results implied that, increasing family strength should he the important factor in pregnancy quality.